Effects of Aerobic Exercise on Sleep Quality, Insomnia, and Inflammatory Markers: A Systematic Review and Meta-Analysis - Mariazel Rubio-Valles; Arnulfo Ramos-Jimenez (Current Issues in Molecular Biology)
Poor sleep quality and insomnia are increasingly linked to chronic inflammation and obesity-related metabolic dysfunction. Aerobic exercise is a promising non-pharmacological approach for enhancing sleep quality and reducing systemic inflammation; Therefore, we aim to systematically evaluate and quantify the effects of aerobic exercise interventions on subjective sleep quality, insomnia severity, and circulating markers (IL-6 and TNF-α) in adults. A systematic search was conducted in institutional databases (UNAM, UACJ) and PubMed to identify randomized controlled trials (RCTs) examining the effects of exercise on sleep and inflammation. Risk of bias was assessed using the Cochrane RoB2 tool. Meta-analyses were performed using RevMan 5.4 with random-effects models to estimate pooled mean differences (MD) and standardized mean differences (SMD), with 95% confidence intervals. Anaerobic protocols were excluded from the meta-analysis due to the insufficient availability of data. : Eleven RCTs met the inclusion criteria. Aerobic exercise showed a significant pooled effect on sleep outcomes (MD = −2.51; 95% CI: −4.80 to −0.23; p = 0.03). However, subgroup analyses for Pittsburgh Sleep Quality Index (PSQI) (MD = −2.27; p = 0.15) and Insomnia Severity Index (ISI) (MD = −2.98; p = 0.16) were not statistically significant. Two studies on IL-6 reported a non-significant reduction (SMD = −0.17; p = 0.66), with moderate heterogeneity. TNF-α results were also non-significant (SMD = 0.60; p = 0.29) with substantial variability. Our results showed that aerobic exercise may modestly improve sleep outcomes; however, current evidence does not support its effectiveness in reducing levels of IL-6 or TNF-α. Further well-controlled trials are needed to clarify its immunometabolic effects, particularly in populations with obesity or metabolic disorders.